# 20x^4y^3-45x^2y^3-5x^2y^2=

## Simple and best practice solution for 20x^4y^3-45x^2y^3-5x^2y^2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 20x^4y^3-45x^2y^3-5x^2y^2= equation:

Simplifying 20x^{4}y^{3}+ -45x^{2}y^{3}+ -5x^{2}y^{2}= 0 Reorder the terms: -5x^{2}y^{2}+ -45x^{2}y^{3}+ 20x^{4}y^{3}= 0 Solving -5x^{2}y^{2}+ -45x^{2}y^{3}+ 20x^{4}y^{3}= 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '5x^{2}y^{2}'. 5x^{2}y^{2}(-1 + -9y + 4x^{2}y) = 0 Ignore the factor 5.## Subproblem 1

Set the factor 'x^{2}y^{2}' equal to zero and attempt to solve: Simplifying x^{2}y^{2}= 0 Solving x^{2}y^{2}= 0 Move all terms containing x to the left, all other terms to the right. Simplifying x^{2}y^{2}= 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.## Subproblem 2

Set the factor '(-1 + -9y + 4x^{2}y)' equal to zero and attempt to solve: Simplifying -1 + -9y + 4x^{2}y = 0 Reorder the terms: -1 + 4x^{2}y + -9y = 0 Solving -1 + 4x^{2}y + -9y = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 4x^{2}y + 1 + -9y = 0 + 1 Reorder the terms: -1 + 1 + 4x^{2}y + -9y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 4x^{2}y + -9y = 0 + 1 4x^{2}y + -9y = 0 + 1 Combine like terms: 0 + 1 = 1 4x^{2}y + -9y = 1 Add '9y' to each side of the equation. 4x^{2}y + -9y + 9y = 1 + 9y Combine like terms: -9y + 9y = 0 4x^{2}y + 0 = 1 + 9y 4x^{2}y = 1 + 9y Divide each side by '4y'. x^{2}= 0.25y^{-1}+ 2.25 Simplifying x^{2}= 0.25y^{-1}+ 2.25 Reorder the terms: x^{2}= 2.25 + 0.25y^{-1}The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

### See similar equations:

| 6m-11=-13+5m | | 20-1a=-10 | | 128=-16t^2+64t+64 | | 0.25x+.05(18-x)=.10(5) | | 7n-13=5+4n | | 44+4x=11+x | | 42=n^2-n | | 20(x+1)=200 | | 2a(x+3y)-b(x+3y)= | | y-12=8 | | M-1=7m+15+2m | | (1/12)/(6/12)= | | 8x+81=6x+95 | | 3x^2+2x-6=2 | | 4-4y+3=-30 | | 3x^2-21xy+2x-14y= | | y=x^2-2-12 | | 5h+6+8h-3h=36 | | 3(x-4)+6(y+1)=21 | | ab-6a+9b-54= | | (10+10x)-15=2x+3 | | 9x^2=-6-1 | | 3-4x=9-5x | | 3x^2+64=0 | | 3x-16+8=-30-15x | | -3=9c | | g+45= | | 2x^2=7-6x | | -14r-7=48 | | (x-4)(3x+1)(x-2)=0 | | 3(x-4)+6(x+1)=21 | | 3(4x-1)=6(x-6) | | 5a-10= | | y=-2.7x+1.5 | | 0.80x+.05(16-x)=.10(-22) | | 3(4x-1)=6(x+6) | | 5y+1=2y+7 | | 105+7=83 | | y-6.5=7.1 | | 10v=-200 | | 10000=19.06+22.73 | | 2m-2=3m | | -9x+6+9x= | | 7x=x+3 | | (3r-6)=21 | | n-15=-10 | | [3r-6]=21 | | 217x=12 | | s=19.06+22.73 | | 8(w-3)=4w | | -8n-2=-5n-8n-9 | | 46-8x=-10 | | -8n-2n=-5n-8n-9 | | -7+-4m=6m+-5 | | x^2+x-1000000=0 | | 3x+12+13=33 | | 100=0.7*x | | x^5-7x^3-18x=0 | | 2p-3p-11=1-3p | | 2x+(-1)+2=4 | | y+7=3(x+4) | | Y-3=4x | | 5x^2-24=7x | | 2x+(-x)2=4 | | -34+73= |